Cultural Hegemony, Liberal Conscience, and Understanding Post - 9/11 American Fiction on Arab Woman - Mubarak Altwaiji (Taez University, 2023)
This article analyses the impact of Post-9/11 political and cultural agendas on writers' attitudes toward Arab woman as a milestone in contemporary scholarship on neo-orientalism. Inspired by the Discourse Theoretical Approach to hegemony and imperialism, this manuscript offers a significant conceptual contribution to studies on the life of Arab women in post-9/11 narratives, City of Veils (2010), as racist, imperial and xenophobic discourse structured around exclusionary visions of the other. With these thoughts in mind, this study focuses on conceptualising the life of Arab woman by Ferraris who has lived in Arabia as a wife of Saudi citizen, as a representative of the climactic epoch in post-9/11 American fiction. It intervenes in debates about the political and cultural value of narratives by showing how post-9/11 narrative project engages specifically with geo-politics and hegemonic agendas. This conceptualisation helps understand how ideologies such as Islamophobia, racism, and populism in post-9/11 narratives all contribute to hegemonic discourse, how hegemonic discourse can be clearly attached with imperialism, and how neo-orientalist authorship can be articulated by writers beyond the neo-orientalist agendas.